Geographies of climate change opinion. Issue 5 (24th March 2022) - Tuitjer, Leonie; Dirksmeier, Peter; Mewes, Lars
Abstract: Climate change can only be tackled with public support for sustainable policies. Thus, public attitudes towards climate change matter. More than 3 decades of climate change opinion (CCO) research—conducted by geographers, environmental psychologists, behavioural scientists, sociologists etc.—have provided us with a wealth of information about which predictors shape public CCOs. This review synthesises these findings and highlights the different geographies (the self, the nation, the region, the digital) that emerge within this research. Given the increased importance of social media, virtual geographies of climate change scepticism are increasingly being identified. Our paper argues that new research agendas must be developed to address the meshwork of virtual space and small scale geographies (regions, towns, districts) in which CCOs are formed.